Study of Banana Stem, Sugarcane Bagasse and Orange Peel as Adsorbent for Treatment of Palm Oil Mill Effluent (POME) Wastewater - Zulkepli, Faezatul Nabila; Mas Rahayu Jalil, (Progress in Engineering Application and Technology, 2023)
Palm oil mills (POME) comprises a high concentration of organic compounds and residual oil, resulting in a high biological oxygen demand (BOD) and chemical oxygen demand (COD). It is dark brownish in color and has a high acidic value and total suspended solids (TSS). Because raw POME is a highly polluting effluent, it cannot be dumped freely and/or directly into any source of water or river without previous adequate treatment [2]. The treatment of raw POME is a critical issue in palm oil mills, and the technique of treatment has drawn the attention of many researchers and non-governmental organizations (NGOs) concerned with environmental contamination. In this study, natural adsorbent is one of the alternative methods in minimizing the usage of chemical adsorbent in water treatment. Banana stem, sugarcane bagasse and orange peels as natural adsorbent help to form a low-cost adsorbent agent for adsorption process in water treatment plant and act as an important environmentally friendly product. The goals of this study are to investigate the effects of dosage of banana stem, sugarcane bagasse and orange peels as natural adsorbent and the maximum pH and the percentage removal of the turbidity and COD in the water sample. The potential of natural adsorbent in removing turbidity in wastewater are tested at a different dosage and pH by using JAR test apparatus. In conclusion, the integration system of conventional POME treatment with bio-adsorbents could be considered as a sustainable approach, thus solving environmental problems of waste disposal and pollution control for the oil palm industry.